Analysis of repeater jamming of a slow frequency hopping radio - Stojanović, Nenad M.; Todorović, Branislav M.; Ristić, Vladimir B. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The article presents a model of a slow frequency hopping radio in the case of repeater jamming. The aim is to analyze the effectiveness of repeater jamming to a military tactical slow frequency hopping radio.Methods: It is assumed that the repeater jammer will be successful in detecting signals with slow frequency hopping at each hop and that it will perform successful partial jamming of the intercepted communication. Under partial jamming, it is considered that a certain part of the transmission time of each hop will be jammed. A theoretical analysis of the impact of a repeater jammer on a frequency hopping radio was performed based on the definition of the total probability of error. Various parameters that affect the segment of hop duration under jamming were considered.Results: The obtained results show that high effective jamming is achieved even when a short segment of hop duration is jammed. We discuss the conditions for the repeater jammer to detect the signal during each hop and emit the jamming signal with the required strength. It has been shown that increasing the frequency hopping rate can significantly reduce the effectiveness of the repeater jammer.Conclusion: Repeater jammers are highly effective against slow frequency hopping radio communication systems.
Keywords: spread spectrum; frequency hopping; repeater jamming; error probability